EVERYDAY LANGUAGE, LITERARY LANGUAGE, AND THE PROBLEM OF TRANSLATION - Krieger, Murray (Surfaces, 1994)
Any understanding of cultures and languages is caught up in the dynamics of translation. This essay outlines the issues of translation in a cross-cultural context and focuses on the relationship between the literary and other modes of discourse as exemplary for understanding issues of cultural translation. In describing the dissolution of the literary into general textuality, it gives a historical overview of the relationship between literary and other discourses from classical to New-Critical and Russian Formalist theories, down to today.